Working with immigrant and refugee families: broadening cross-cultural understanding with immigrant/refugee families - Margarita Machado-Casas; Sergio Andrés Cabello; Katherine Talati-Espinza; Haetham Abdul-Razaq (FahrenHouse, 2018)
Parent engagement programs are in high demand these days, particularly as they pertain to immigrant and refugee families. But working with families entails purposeful communication with families (Valdés, 1996). Yet, often families are caught in cross-cultural divides that forces them out of engagement with those running the program (Machado-Casas, 2012). Cultural disconnections often times become ways in which minority families find themselves trapped (Nieto & Bode, 2011). Some researchers have looked at non-traditional pedagogical spaces to challenge future and practicing educators and community members to examine how the process of normalization privileges dominant groups while simultaneously oppressing 'others' (Cary, 2006). When this happens the process of «pimping families» through discourses that «talk» at them rather than to/for them lead to furthering hegemonic practices often aimed at minority families. Through interviews with families, and educators, this paper will highlight the «cultural confessions» of educators, and families who utilize non-traditional spaces to expose how prejudice and privilege have influenced their perceptions of «legitimate knowledge», legitimate spaces, and legitimate cross-cultural communication. This paper will present data obtained form Communities United for Education (CUPE) a family involvement and education program that nurtures a strong sense of community among students, teachers, and families. The program focuses in the empowering of families through developing support, leadership, advocacy, and activism, in addition to working with parents on bridging the digital divide among family members. Data presented will expose how families have educators have experienced and dealt with cross-cultural communication issues.